2012
DOI: 10.1097/aog.0b013e31824da5a8
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Visual Functioning After Eclampsia

Abstract: OBJECTIVE:Complete neurocognitive recovery after eclampsia has been questioned with the expression of neurocognitive deficits by affected women and demonstration of cerebral white matter lesions on magnetic resonance imaging years after eclampsia. We hypothesized that formerly eclamptic women may experience impaired vision-related quality of life (QOL) and visual field loss as a result of the presence of such lesions in the cerebral visual areas. METHODS:Using the National Eye Institute Visual Function Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Three to eight months after severe pre‐eclampsia, women have measurably impaired memory which is unrelated to scores of depression, anxiety or attention . Women who have had eclampsia self‐report more cognitive failures and impaired vision several years after pregnancy compared to those women who had pre‐eclampsia or normal pregnancies …”
Section: Long‐term Consequencesmentioning
confidence: 99%
“…Three to eight months after severe pre‐eclampsia, women have measurably impaired memory which is unrelated to scores of depression, anxiety or attention . Women who have had eclampsia self‐report more cognitive failures and impaired vision several years after pregnancy compared to those women who had pre‐eclampsia or normal pregnancies …”
Section: Long‐term Consequencesmentioning
confidence: 99%
“…it has been shown that, several years later, formerly preeclamptic and eclamptic women report cognitive failures related to memory, attention, and vision-related tasks of everyday life (Andersgaard et al, 2009;Aukes, Wessel, Dubois, Aarnoudse, & Zeeman, 2007;Postma, Bouma, Ankersmit, & Zeeman, 2014;Postma et al, 2013;Wiegman et al, 2012). In the literature, small studies evaluating neurocognitive test performance in preeclamptic women within 1.5 years following the index pregnancy have found impairment pertaining to auditory-verbal memory (Brussé, Duvekot, Jongerling, Steegers, & De Koning, 2008), speed of information processing (Digit Symbol Coding of Wechsler Adult Intelligence Scale-Third Edition, Dutch Version, WAIS-III-NL), and divided attention (Paced Auditory Serial Addition Test; Baecke, Spaanderman, & Van der Werf, 2009), but not on other cognitive tests.…”
mentioning
confidence: 99%
“…It is defined as new-onset hypertension combined with proteinuria after the 20th week of pregnancy. [7][8][9] Whether these symptoms are related to the PRES episode is unknown. Eclampsia is an acute cerebral complication of preeclampsia, defined as the occurrence of tonic-clonic seizures in pregnant or recently postpartum women.…”
Section: Background and Aimsmentioning
confidence: 99%